Prognostic value of human papillomavirus 16/18 genotyping in low-grade cervical lesions preceded by mildly abnormal cytology - Ye, Jing (Zhejiang University Press, 2017)

(untitled) (J Zhejiang Univ Sci B)
Histological low-grade squamous intraepithelial lesion/cervical intraepithelial neoplasia grade 1 (LSIL/CIN1) preceded by normal or mildly abnormal cytology is recommended for conservative follow-up, with no separated management. In this study, we assessed the triage value of human papillomavirus (HPV) 16/18 genotyping in 273 patients with LSIL/CIN1. HPV16/18 genotyping was performed at baseline and follow-up was at 6-monthly intervals for up to 2 years. At each follow-up, women positive for cytology or high-risk HPV (hrHPV) were referred for colposcopy. Enrollment cytology, HPV16/18 genotyping, and questionnaire-obtained factors were linked to the 2-year cumulative progression rate. Univariate and multivariate analyses were performed taking into account time-to-event with Cox proportional hazard regression. The results showed that 190 cases (69.6%) regressed, 37 (13.6%) persisted, and 46 (16.8%) progressed. HPV16/18 positivity (hazard ratio (HR), 2.708; 95% confidence interval (CI), 1.432–5.121; P=0.002) is significantly associated with higher 2-year cumulative progression rate. Sub-analysis by enrollment cytology and age restricted the positive association among patients preceded by mildly abnormal cytology and aged 30 years or older. Immediate treatment is a rational recommendation for the high-risk subgroup, when good compliance is not assured.